Nonlinear dynamics based digital logic and circuits - Kia, Behnam; Lindner, John. F.; Ditto, William L. (Frontiers in Computational Neuroscience, 2015)
We discuss the role and importance of dynamics in the brain and biological neural networks, and argue that dynamics is one of the main missing elements in conventional Boolean logic and circuits. We summarize a simple dynamics based computing method, and categorize different techniques that we have introduced to realize logic, functionality, and programmability. We discuss the role and importance of coupled dynamics in networks of biological excitable cells, and then review our simple coupled dynamics based method for computing. In this paper, for the first time, we show how dynamics can be used and programmed to implement computation in any given base, including but not limited to base two.